2019
DOI: 10.1007/s40471-019-00201-9
|View full text |Cite
|
Sign up to set email alerts
|

Methodological Complexities in Quantifying Rates of Fatal Opioid-Related Overdose

Abstract: Purpose of Review Effective responses to the US opioid overdose epidemic rely on accurate and timely drug overdose mortality data, which are generated from medicolegal death investigations (MDI) and certifications of overdose deaths. We identify nuances of MDI and certification of overdose deaths that can influence drug overdose mortality surveillance, as well as recent research, recommendations, and epidemiological tools for improved identification and quantification of specific drug involvement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 54 publications
0
30
0
1
Order By: Relevance
“…The prevalence of alcohol use disorder is highest in Europe (7.5%) and the lowest among East Mediterranean Regions which includes Afghanistan, Bahrain, and Egypt [1]. In the US, the largest national economy of the world, 75% of high-school students have reportedly used illegal drugs, drunk alcohol or smoked tobacco [8], more than a million used heroin in 2016 [9] and opioids claim 70,000 death from overdose in 2017 [10,11]. Bangladesh is situated in the crucial point between the 'golden triangle' (Myanmar, Thailand and Laos) and the 'golden crescent' (Pakistan, Afghanistan and Iran) in terms of geographical location [12].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of alcohol use disorder is highest in Europe (7.5%) and the lowest among East Mediterranean Regions which includes Afghanistan, Bahrain, and Egypt [1]. In the US, the largest national economy of the world, 75% of high-school students have reportedly used illegal drugs, drunk alcohol or smoked tobacco [8], more than a million used heroin in 2016 [9] and opioids claim 70,000 death from overdose in 2017 [10,11]. Bangladesh is situated in the crucial point between the 'golden triangle' (Myanmar, Thailand and Laos) and the 'golden crescent' (Pakistan, Afghanistan and Iran) in terms of geographical location [12].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has identified several methodological challenges for identification of opioid involvement in drug overdose deaths (e.g., lack of routinely performed postmortem toxicology testing, especially for fentanyl and designer opioids; challenges to detection and quantification of new designer opioids; variation in jurisdictional office policy in completion of drug overdose death certificates; differences in the proportion of drug overdose death certificates completed by different jurisdictions that do not list the specific contributing drugs) ( Buchanich et al, 2018 ; Ruhm, 2018 ; Slavova et al, 2015 ; Slavova et al, 2019 ; Warner and Hedegaard, 2018 ; Warner et al, 2013 ). Prior to the evaluation period, the research sites are administering surveys among the coroners, medical examiners, and toxicology labs serving both Wave 1 and Wave 2 communities to collect information related to death investigations of suspected drug overdose deaths (including postmortem toxicology testing, timelines for death certificate completion, and possible COVID-19-related changes in these processes that could have lasting effects during the HCS evaluation period) in order to understand possible limitations and changes in the completeness and accuracy of the primary outcome measure.…”
Section: Resultsmentioning
confidence: 99%
“…The CDC estimates that one in three death certificates are in error [14]. Other studies suggest even higher error rates, especially when dealing with opioid overdose deaths [15]. Death certificates require a single cause of death, but allow for secondary causes.…”
Section: The Datamentioning
confidence: 99%